2022
DOI: 10.1177/21582440221091251
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effects of Information Systems Usage and Managerial Commitment on Supply Chain Performance: The Mediating Role of Supply Chain Integration

Abstract: The aim of the study is to investigate the effect of Information Systems Usage on Supply Chain. Information systems involve creating specific environment for the fulfilment of organizational strategy. However, information system affords an organization an enormous benefit that materializes in the long-run. Unfortunately, realization of information system is also accompanied with risk which mostly deters management from taking the initiative hence missing out on the intended benefits of implementing information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 82 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…Therefore, the 4 th hypothesis of the research was accepted. This result is in agreement with the findings of Vanichchinchai and Igel (2011), Masindet and Ogullah (2014), Rajab (2015), Fouad et al (2015), Hashemi et al, (2022), Leksono et al, (2022), Qureshi (2022), Som and Anyigba (2022), Uddin (2022), Uddin and Akhter (2022), Zhang et al, (2022) Lyu et al, (2023 who indicated that management commitment influences the performance of the supply chain in manufacturing sector.…”
Section: H3: Customer Focus Impacts Supply Chain Performancesupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, the 4 th hypothesis of the research was accepted. This result is in agreement with the findings of Vanichchinchai and Igel (2011), Masindet and Ogullah (2014), Rajab (2015), Fouad et al (2015), Hashemi et al, (2022), Leksono et al, (2022), Qureshi (2022), Som and Anyigba (2022), Uddin (2022), Uddin and Akhter (2022), Zhang et al, (2022) Lyu et al, (2023 who indicated that management commitment influences the performance of the supply chain in manufacturing sector.…”
Section: H3: Customer Focus Impacts Supply Chain Performancesupporting
confidence: 92%
“…In line with findings of Hashemi et al, (2022), Leksono et al, (2022), Qureshi (2022), Som and Anyigba (2022), Uddin (2022), Uddin and Akhter (2022), Zhang et al, (2022) and Lyu et al, (2023), there are a significant influence of management commitment on the supply chain performance. According to this significant relationship, the final hypothesis of the research was formulated as follows:…”
Section: 5supply Chain Performance and Customer Focussupporting
confidence: 75%
See 1 more Smart Citation
“…DREAM JOURNAL -VOL. 02, ISSUE 09, 2023 Moreover, the Resource-Based View (RBV) are fundamental theoretical frameworks that elucidate the manner in which organisations engage in value creation and capture in the pursuit of their strategic and operational goals (Som & Anyigba, 2022). RBV, which is based on two fundamental principles that elucidate the mechanisms through which firm-specific resources generate enduring competitive advantage and the reasons behind certain organisations consistently surpassing others in terms of competitiveness (Utami & Alamanos, 2023), is complemented by RV, a study of relational strategies that originates from the field of strategic management (Zakrzewska-Bielawska & Lewicka, 2021).…”
Section: ) the Resource-based View (Rbv)mentioning
confidence: 99%
“…The use of Information System (IS) 25 in healthcare is in the digitalization of healthcare. Healthcare industry is adopting IS to replace the manual processing.…”
Section: Healthcare Information System Securitymentioning
confidence: 99%